Impulsive boundary-value problems for weakly nonlinear systems with control - Kozachenko, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
For weakly nonlinear impulsive differential systems with control, we obtain necessary and sufficient conditions for the existence of control and the corresponding solutions of differential systems with general boundary conditions.